2021
DOI: 10.1113/jp281385
|View full text |Cite
|
Sign up to set email alerts
|

Regulated hypothermia in response to endotoxin in birds

Abstract: The costs associated with immune and thermal responses may exceed the benefits to the host during severe inflammation. In this case, regulated hypothermia instead of fever can occur in rodents as a beneficial strategy to conserve energy for vital functions with consequent tissue protection and hypoxia prevention.r We tested the hypothesis that this phenomenon is not exclusive to mammals, but extends to the other endothermic group, birds.r A decrease in metabolic rate without any failure in mitochondrial respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 87 publications
1
5
0
Order By: Relevance
“…Even though the chicks were exposed to T a s in the range that this thermoreceptor is shown to sense in vivo (Vizin et al, 2015), 31 and 26 °C do not represent a warm T a for the 5day-old chicks. In fact, a T a of 26 °C triggers activation of thermogenesis instead of thermolysis in the first week of life in chicks (Amaral-Silva et al, 2021;Cristina-Silva et al, 2021; Amaral-Silva et al, 2022). Thus, these animals are not expressing any heat loss response, which would be inhibited by HC06747 in the case where TRPV4 was active, and T b would be consequently increased by the lack of this response.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Even though the chicks were exposed to T a s in the range that this thermoreceptor is shown to sense in vivo (Vizin et al, 2015), 31 and 26 °C do not represent a warm T a for the 5day-old chicks. In fact, a T a of 26 °C triggers activation of thermogenesis instead of thermolysis in the first week of life in chicks (Amaral-Silva et al, 2021;Cristina-Silva et al, 2021; Amaral-Silva et al, 2022). Thus, these animals are not expressing any heat loss response, which would be inhibited by HC06747 in the case where TRPV4 was active, and T b would be consequently increased by the lack of this response.…”
Section: Discussionmentioning
confidence: 99%
“…When TRPV4 was chemically stimulated at 19 °C, adult chickens decreased T b , similarly to what was observed in chicks. This response in the adults relied on the activation of tachypnea, providing evaporative heat loss (Wolfenson et al, 1981;Arad and Marder, 1982), and also on metabolic rate inhibition, reducing heat gain (Amaral-Silva et al, 2021;Amaral-Silva et al, 2022). In this case, the pharmacological effect of the TRPV4 agonist may be more potent to stimulate the specific skin sensors for activating those thermoeffectors than stimulation by the warm condition at 28 °C.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although several studies report an increase in metabolic rate, and a decrease in food intake and body mass after LPS inoculation, there was a great variability in the magnitude of these responses among species (Volkoff and Peter 2004;Burness et al 2010;Llewellyn et al 2011;Marais et al 2011;MacDonald et al 2012;King and Swanson 2013). On the other hand, not all studies have reported that LPS triggers fever, increases metabolic rate, activates the HPA axis (hypothalamic-pituitary-adrenal), or increases the total white blood cell count (Weber et al 2005;Copeland et al 2005;Krams et al 2012;Stockmaier et al 2015;Rakus et al 2017;Lind et al 2020;Amaral-Silva et al 2021). Some of these differences certainly reflect species-specific differences and they are contingent on the specific context of the study.…”
Section: Introductionmentioning
confidence: 99%